Mediterranean X Western based diets: Opposite influences on opioid reinstatement. (15th June 2019) - Milanesi, Laura Hautrive; Rossato, Domenika Rubert; Dias, Verônica Tironi; Kronbauer, Maikel; D'avila, Lívia Ferraz; Somacal, Sabrina; Duarte, Thiago; Duarte, Marta Maria Frescura; Emanuelli, Tatiana; Burger, Marilise E.
Highlights: Western diets evoke anxiety behaviors and activate HPA axis, favoring morphine addiction. Western diets facilitate morphine withdrawal symptoms such as locomotor sensitization and thermal sensitivity. Western diets induce morphine-reinstatement and modify DA neurotransmission. Mediterranean-diet prevents morphine-reinstatement. Abstract: Opioids are addictive drugs, whose misuse evoke withdrawal and relapse. Mediterranean-based diet (MBD) is rich in n-3 polyunsaturated fatty acids (PUFA), while Western based diets (WBDs) contain saturated fatty acids including interesterified fat (IF) and palm oil (PO), influencing neural functions. We compared MBD and WBDs on morphine-induced addiction parameters. Rats fed with MBD (chow plus 20% soybean- and fish-oil- n-6/n-3 PUFA 1:1) or WBD (WBD- PO or WBD-IF: chow plus 20% of palm oil or interesterified fat, respectively; high n-6/n-3 PUFA ratio) were exposed to morphine in conditioned place preference (CPP) paradigm. Anxiety-like behavior, locomotion and thermal sensitivity were evaluated during withdrawal. After morphine-CPP extinction, animals were challenged to morphine-reinstatement to induce relapse. All groups showed morphine-CPP, WBDs favored anxiety-like behaviors per se, locomotor sensitization and thermal hipersensitivity during withdrawal, resulting in increased morphine-reinstatement in comparison to MBD, which did not show relapse. WBDs increased glucocorticoid receptor immunoreactivity in the pre-frontal cortex, increasing corticosterone (CORT) and adrenocorticotrophic hormone (ACTH) per se and after morphine-reinstatement. In the nucleus accumbens, WBDs increased dopamine transporter (DAT) and dopamine receptor-2 (D2R) immunoreactivity and decreased dopamine receptor-1 (D1R). These findings indicate that WBDs facilitate morphine-reinstatement, unlike MBD, preserving the DA system mesolimbic neuroplasticity.